Understanding the FLASH effect to unravel the potential of ultra-high dose rate irradiation - Kacem, Houda; Almeida, Aymeric; Cherbuin, Nicolas; Vozenin, Marie-Catherine (International journal of radiation biology, 2022)
A reemergence of research implementing radiation delivery at ultra-high dose rates (UHDRs) has triggered intense interest in the radiation sciences and has opened a new field of investigation in radiobiology. Much of the promise of UHDR irradiation involves the FLASH effect, an in vivo biological response observed to maintain anti-tumor efficacy without the normal tissue complications associated with standard dose rates. The FLASH effect has been validated primarily, using intermediate energy electron beams able to deliver high doses (>7 Gy) in a very short period of time (<200 ms), but has also been found with photon and proton beams. The clinical implications of this new area of research are highly significant, as FLASH radiotherapy (FLASH-RT) has the potential to enhance the therapeutic index, opening new possibilities for eradicating radio-resistant tumors without toxicity. As pioneers in this field, our group has developed a multidisciplinary research team focused on investigating the mechanisms and clinical translation of the FLASH effect. Here, we review the field of UHDR, from the physico-chemical to the biological mechanisms.